CircUBAP2 Promotes MMP9-Mediated Oncogenic Effect via Sponging miR-194-3p in Hepatocellular Carcinoma - Liu, Boqiang; Tian, Yuanshi; Chen, Mingyu; Shen, Hao; Xia, Jiafeng; Nan, Junjie; Yan, Tingting; Wang, Yifan; Shi, Liang; Shen, Bo; Yu, Hong; Cai, Xiujun (Frontiers in Cell and Developmental Biology, 2021)
Background: The physiological regulatory functions of circRNAs have become a topic of intensive research in recent years. Increasing evidence supports a significant role of circRNAs during cancer initiation and progression, including hepatocellular carcinoma (HCC). Methods: A bioinformatics analysis from three independent Gene Expression Omnibus (GEO) databases was performed to profile and screen the dysregulated circRNAs in HCC. RT-qPCR was used to examine the expression level of circUBAP2 in HCC and adjacent non-tumor tissues. Then, proliferation assays (CCK8 and colony formation) and migration assays (transwell and wound healing) were performed to examine effect of circUBAP2 in vitro. Immunoprecipitation, RNA pulldown, FISH and dual-luciferase reporter assay was conducted to explore the circUBAP2-related mechanism for regulating HCC progression. Moreover, a mouse xenograft model and a mouse lung metastasis model confirmed the effect of circUBAP2 in vivo. Results: In this study, we found a novel circRNA: circUBAP2, which was identified by bioinformatics analysis. Among 91 HCC patients, circUBAP2 was significantly upregulated in HCC tissues, and negatively correlated with aggressive clinical characteristics and prognosis. Functional assays demonstrated that circUBAP2 promoted cell proliferation, colony formation, migration and invasion in vitro. Moreover, circUBAP2 enhanced tumor growth and pulmonary metastasis in vivo. Mechanistically, circUBAP2 acts as a competing endogenous RNA (ceRNA) for miR-194-3p, a tumor suppressor in HCC. We confirmed that MMP9 was direct target for miR-194-3p, which was regulated by circUBAP2. Conclusions: CircUBAP2 plays a significant role in promoting HCC via the miR-194-3p/MMP9 pathway and could serve as a promising prognostic biomarker and novel therapeutic target for HCC patients.